(3OhQ eTQhYGJ GdJfejI GdeUQjI ` GdJfRGfjI ai JTcjd GdUhQI GdPgfjI Yf eUQ dOi GdTYH GdJfRGfi (B:s (3OQGSI ejOGfjI ai GdCfKQhHhdhLjG GdKbGajI (B/s - (3,gfGA YHO GdMejO eMeO SYjO MeGOs; (3EjeGf GdHSWhjSis; (3YdjGA GdMSjf s; (3SMQ eMeO ZQGHs (2024)
(3gOaJ gPg GdOQGSI, Edi GdJYQa Ydi JCKjQ eTQhYGJ GdJfejI GdeTJQcI , Hjf eUQ hJfRGfjG HTcd YGe Ydi GdUhQI GdPgfjI GdJi JchfJ dOi GdTYhH GdJfRGfjI, hcCdjI ef CdjGJ GdJYGhf hGdEMJcGc GdeHGTQ Hjf GdTYhH GdCaQjbjI, hbOQI Jdc GdeTQhYGJ Ydi GdJCKjQ Ydi JhLgGJge hCQGFge hfXQJge dCi ehVhY Ch bVjI JNU eUQ, hbO EYJeOJ GdOQGSI Ydi eLehYI ef GdefGgL hGdfXQjGJ, hGdJi JeKdJ ai GdefgL GdCfKQHhdhLi HCOhGJ GdHMK GdejOGfjI, hGdefgL GdhUai GdJMdjdi, hGdefgL GdJGQjNi, hbO EYJeOJ GdOQGSI Ydi eONd QDi GdYGde ceONd fXQi (B.(3hbO CLQjJ OQGSGJ ejOGfjI Hjf KdGK CbGdje JfRGfjI, hbO JhUdJ GdOQGSI Edi GdYOjO ef GdfJGFL GdegeI, Mhd CgejI eTQhYGJ GdJfejI GdeUQjI ` GdJfRGfjI , ai JTcjd UhQI PgfjI Yf eUQ,h Mhd GdJZjQGJ GdEbJUGOjI hGdKbGajI hGdELJeGYjI, hGdOjfjI ai HYV GdCMjGf, hGdJi JYJHQ HTcd CSGSi cfJjLI deTQhYGJ GdJfejI GdeTJQcI(B.s
This study aimed to identify the impact of joint development projects between Egypt and Tanzania, in general on the mental image formed by the Tanzanian peoples, as a mechanism of cooperation and direct contact between African peoples, and the ability of these projects to influence their orientations, opinions and views on any topic or issue related to Egypt.The study relied on a set of approaches and theories, which were represented in the anthropology Field studies were conducted in three Tanzanian regions, and the study reached many important results, about the importance of Egyptian-Tanzanian development projects, in forming a mental image of Egypt, and about the economic, cultural, social, and sometimes religious changes, which are considered basically as a result of joint ological approach with field research tools, the descriptive analytical approach, and the historical approach. The study relied on the world visions approach as a theoretical approach.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B169-176.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdCfKQHhdhLjG GdKbGajIs; (3eTQhYGJ GdJfejIs -- (3GdUhQI GdPgfjIs -- (3eUQs